Pengaruh Media Sosial Instagram dan Electronic Word of Mouth Terhadap Minat Berkunjung Objek Wisata Setigi Gresik - Nasyifa Nasyifa; Suyono Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
Research based on the lack of content provision and the provision of extensive information on social media is the main reason between the onslaught of competition and the use of social media that can be used to increase interest in visiting Setigi tourism objects. The aim was to determine the level of interest in visiting Setigi tourism objects based on the results of using and obtaining information from the social media Instagram and the presence of electronic word of mouth. The variables in this study is social media Instagram and electronic word of mouth variables, which became independent variables, while the dependent variable was interest in visiting Setigi Gresik tourism objects. This study uses a quantitative approach method using SPSS statistical calculations with a total of 99 respondentsThe results that have been found based on the existing problems are that there is a significant influence between Instagram social media variables on visiting interest, the electronic word of mouth variable has also had a significant influence. significant to the interest in visiting, as well as the simultaneous influence of the independent variables on the dependent variable.